PERANCANGAN MODEL KINERJA PENGOLAHAN LIMBAH COOLANT DENGAN PENDEKATAN SYSTEM DYNAMICS ( STUDI KASUS : SEKSI MACHINING –PLANT PEGANGSAAN PT ASTRA HONDA MOTOR ) - Rusman Kosasih (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
Indonesian manufacturing industries have to comply with good responsibilites ofmanagement of the environtment. Strategically, the limitation standard for quality of industrial wastewater, the document of Environmental Impact Assessment, Environmental Management Effort -Environmental Monitoring is some evidence of the Government's efforts to set a good environmentalmanagement. Technically, the engineering processes to 6R (Refine - Reduce - Reuse - Recycle -Recovery - Retrieve energy) into one of the flagship activities to help realize environmentalmanagement in accordance with Government Regulation. PT Astra Honda Motor is a companyengaged in manufacturing Honda motorcycles. Motorcycle production increases seizing with thegrowth of market needs. This results in increased production of liquid waste coolant from themachining process, exceeding the capacity of Inplant Waste Water Treatment System. Machiningsection develop Recycle Instalation to process waste coolant to be used again in the machiningprocess. This research aims to design Recycle installation processing performance models with systemdynamics approach. Desired processing performance indicators are indicators of quality andproductivity of coolant Recycle process. The research method carried out by conducting a preliminarystudy, design of Causal Loop Diagram, Model design based on system dynamics approach.Verification of the model is done by determining whether the interaction variable models can reflectreal events. Model validation is done by comparing the results of model performance indicator withthe results performance indicator of actual processing. Several alternative processing strategies andpolicies expected to be made to anticipate fluctuations in production in the future while maintainingthe performance indicators of quality standards of coolant recycle and productivity of Recycleprocess.